THE EFFECT OF EMPOWERMENT OF PREGNANT WOMEN IN THE COMMUNITY ON ANTENATAL CARE COMPLIANCE - Evita Widyawati; Oktaviana Manda Putri; Friska Oktaviana (Jurnal Smart Kebidanan, 2025)
Participation of pregnant women in antenatal care can support maternal and fetal health. However, low compliance rates indicate a lack of adequate care in the community. This study aimed to assess the effect of an empowerment program for pregnant women on adherence to antenatal care in the Kedungwaru Community Health Center (Puskesmas) area, Kedungwaru District, Tulungagung Regency. The study design was a one-group pre-experimentary study, consisting of a pre-test and a post-test. A total of 40 pregnant women were selected as the sample using purposive sampling. A questionnaire was used to collect information, while the Wilcoxon test was used to analyze the data. Increased adherence to antenatal care and participation in the empowerment program each showed significant results with a p-value of 0.000 (p < 0.05). The empowerment program for pregnant women increased adherence to antenatal care. This program should be expanded because it promotes better maternal health education and preventive health practices in the community.